CHEMICAL SCIENCE AND ENGINEERING TECHNOLOGY : Perspectives on Interdisciplinary Research - Balks̲e, Devrim, editor; Ribeiro, Ana Cristina Faria, editor; Haghi, A. K., editor; Ameta, Suresh C., editor; Chakraborty, Tanmoy, editor (Oakville, ON ; Palm Bay, Florida : Apple Academic Press, 2019)
Includes bibliographical references and index.